The significance of self-fulfilling science - Lowe, Charles (2018)
Once lively debates concerning the philosophical significance of self-fulfilling science, or the causal contribution of science to bringing about the states of affairs it depicts, lapsed in the 1970s. Recent claims concerning the influence of economic theory on the behavior it predicts or explains seem poised to revitalize discussion, yet lack of clarity abounds concerning the key features of such cases and the philosophical issues to which they might be relevant. In this paper, I examine a paradigmatic case of self-fulfilling science, clarify its key features, and critically discuss two existing approaches to understanding such phenomena. Ultimately, I suggest a novel approach more well-suited to analyzing such cases and exploring their philosophical significance. - Reproduced.
Keywords: Ethics; Science; Values